Chapter Ascetism and Incontinence and Dostoevsky's Gift of Tears - Apollonio, Carol (Biblioteca di Studi Slavistici, 2023)
In Dostoevsky's binary poetics, an opposition can be drawn between two fundamental stances - asceticism and incontinence. Ascetics adhere to an ethos of self-restraint in response to the desires of the flesh. Incontinents act spontaneously to gratify their desires. The current study draws an analogy between the behavior pattern of Dostoevsky's self-denying intellectual heroes and that of exiled castrate (skoptsy) communities. Dostoevsky's ascetics represent a cerebral mindset attracted to visions of social utopia; their intellectualizing detaches them from the life of the body and thus weirdly parallels the strictures of the skoptsy. An encounter between an ascetic and a prostitute serves as a central plot moment in works such as Crime and Punishment and Notes from Underground.